Food Quality, Price Fairness, and Service Quality as Drivers of WoM Intention through Customer Satisfaction on Mie Gacoan in Indonesia - Farah Adnina; Rasya Safira Ishamiyya; Silvia Rahma Dewi (Jurnal Administrasi Bisnis)
The F&B industry faces intense competition, with the Business Competition Index reaching 4.91% (Komisi Pengawas Persaingan Usaha, 2024). Strategies in food quality, price fairness, and service quality are key to competitive advantage, especially for Gacoan Noodles as the market leader in spicy noodles. This study analyzes the effect of food quality, price fairness, and service quality on customer satisfaction and its impact on word-of-mouth (WoM) intentions, with customer satisfaction as a mediating variable. The respondents of this study were 177 customers of Mie Gacoan. The data were analyzed using the Partial Least Squares (PLS) method with SmartPLS version 3. The results showed that food quality, price fairness, and service quality have a positive and significant effect on customer satisfaction. Customer satisfaction also mediates the relationship of the three variables with WoM intention. The practical implication of this study is that Mie Gacoan needs to improve food quality, set fair prices, and optimize services to increase customer satisfaction and encourage positive WoM. Future research is suggested to expand the sample coverage by comparing similar restaurants and considering other factors such as customer experience and involvement in online communities.